Pelatihan Pembuatan Google Form bagi Guru di SMP Negeri 7 Merauke sebagai Media Evaluasi Pembelajaran Jarak Jauh (PJJ) - Christiana Normalita de Lima; Dharma Gyta Sari Harahap; Darmalis Marlissa (Jurnal Transformasi Pendidikan Indonesia, 2023)
Distance learning in the era of digitalization has now become one of the mechanisms that many educational institutions choose in the learning process. During the Covid era, distance learning or what we know as PJJ is one of the alternatives used to provide rights for students even though there is no direct meeting. This community service was carried out with the aim of providing training to teachers at SMP Negeri 7 Merauke as an evaluation tool in the Distance Learning (PJJ) process. The application of this learning is not as easy as many people talk about, because teachers must be able to choose and design learning media using technology. The problem experienced by teachers, especially in the regions, is the lack of knowledge in creating technology-based learning media, especially learning media that can be used as evaluation material for Distance Learning (PJJ). As a solution to overcome this problem, our team held training on creating Google Forms for teachers as a medium for evaluating Distance Learning (PJJ). The method we provide for this community service activity is by providing direct training to teachers, creating simple modules, and providing assistance in creating Google Form evaluation media. The result of this service activity is that the 25 teachers who took part in the training were able to create and design their own Google Forms according to the needs of each subject as a medium for evaluating Distance Learning (PJJ). Apart from that, based on the results of questionnaires filled out by teachers who took part in the training, it showed that 90% of the teachers understood how to create their own Google Forms and the teachers were happy and enthusiastic about the training activities carried out